2012
DOI: 10.1161/circinterventions.112.973305
|View full text |Cite
|
Sign up to set email alerts
|

Response to Michiels et al and Sen et al Regarding Article, “Diagnostic Accuracy of Combined Intracoronary Pressure and Flow Velocity Information During Baseline Conditions: Adenosine-Free Assessment of Functional Coronary Lesion Severity”

Abstract: We would like to thank the correspondents for their interest in our work.1 The debate on adenosine may well be an important factor hampering adoption of physiologically guided revascularization, and therefore the value of a vasodilator-free approach deserves consideration in the light of its possible clinical implications. However, we welcome the criticism employed by the correspondents, as we agree that a rise in adoption must not go hand-in-hand with a fall in accuracy. As such, although our results are favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…However, our results indicate that iFR, FFR, and iFRa had equivalent agreement in diagnostic classification with HSR. This observation is in keeping with other recent independent studies, which have also shown that diagnostic categorization agreement is not necessarily improved after the administration of pharmacological vasodilators (28).…”
Section: Figuresupporting
confidence: 93%
“…However, our results indicate that iFR, FFR, and iFRa had equivalent agreement in diagnostic classification with HSR. This observation is in keeping with other recent independent studies, which have also shown that diagnostic categorization agreement is not necessarily improved after the administration of pharmacological vasodilators (28).…”
Section: Figuresupporting
confidence: 93%
“…In addition, recent studies found an equivalent agreement between iFR and FFR, when compared to HSR as a standard of reference [40,50]. Accordingly, van de Hoef and colleagues reported the non-hyperemic stenosis resistance index to be as accurate as fractional flow reserve or coronary flow velocity reserve when compared against myocardial perfusion scintigraphy as the standard of reference [51]. Most importantly, an iFR-guided strategy should be compared head to head with a FFR-guided strategy on clinical endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BSR and FFR have similar levels of diagnostic accuracy for the identification of inducible ischaemia, as established by the area under the curve (AUC) from receiver operating characteristics against myocardial perfusion scintigraphy (AUC 0.77 for both). However, the investigators also suggested that the diagnostic accuracy of BSR was improved (AUC 0.81, P < 0.05) by hyperaemia [hyperaemic stenosis resistance index (HSR)], albeit it is less dependent than FFR on the extent of hyperaemia achieved [19,31]. FFR (cutoff < 0.75) and BSR showed similar false-positive (16 vs. 14%) and falsenegative rates (10 vs. 11%) in this data set.…”
Section: Nonhyperaemic Indicesmentioning
confidence: 73%
“…The stenosis resistance index is calculated as the ratio of the pressure gradient to the distal flow velocity [19]. It has been reported that BSR and FFR have similar levels of diagnostic accuracy for the identification of inducible ischaemia, as established by the area under the curve (AUC) from receiver operating characteristics against myocardial perfusion scintigraphy (AUC 0.77 for both).…”
Section: Nonhyperaemic Indicesmentioning
confidence: 99%
See 1 more Smart Citation